Refugee crises and third-world economies : policies and perspectives - Kumar Das, Sourav; Chowdhary, Nidhi (Emerald Publishing Limited, 2020)
The global political economy is currently in the midst of a refugee crisis, one that is complex and that remains poorly researched and under-theorized within both economics and political science. There is little understanding of the many diverse political, economic and geographical situations that led to it, and refugees are all too often included in the category of forced migrants. Refugee Crisis and Third-World Economies provides a much-needed corrective to such blind spots and oversimplifications. The ten chapters written by eminent scholars offer a unique interdisciplinary investigation into the complicated ramifications of the refugee crisis. It identifies the major socio-political factors that create refugee crises, including political instability, unemployment, a lack of GDP growth, and a lack of medical facilities. It offers unique insights into the crisis's economic impact on asylum countries. It discusses how relevant states, UN agencies, NGOs, and refugees themselves can work together to improve the lot of refugees. And perhaps most importantly, it provides detailed empirical investigations into specific refugee groups and their struggle for legal assistance, socio-political recognition, and personal stability. For its theoretical rigor and granular empirical insights, this book is essential reading for both researchers and policymakers working on refugee crises worldwide.